ANALISIS POSTUR KERJA PADA UKM KERAJINAN COR ALUMINIUM - Amarria Dila Sari (Teknoin, 2017)
The work process in some aluminum cast aluminum craft shows a series of work that has the risk of injury. UKM Aluminum Correct Handicraft Correct in Bantul, Yogyakarta, untouched in the manufacture of household appliance such as wok as its output. SMEs are divided into several work processes, namely smelting, printing, pengikiran, lathe, brand attachment, and packing. From the results of preliminary observations, the problems encountered in the production process are with potential ergonomic hazard (ergonomic hazard). The posture and work area (less) are less ergonomic as well. The purpose of this study is the prevention of ergonomic hazards, especially with the analysis of work postures that can cause the risk of injury. The results of the work posture category on SME aluminum casting on operators 1 and 2 enter the acceleration category level 3 which requires immediate examination, while operator 3 enters in action level 2 (continued). Terms of repair work system on aluminum cast aluminum that is by changing the work station from work station stands to work station sitting stand at work station finishing and also add chair and table at work of thinking. Also note the stretching and periodic rest.